Development of Oil Palm Based Biomass Technology for Renewable Energy Harvesting - Azuwien Aida Bohari; Emier Nurman Hazeem; Muhammad Rusydi Muhammad Razif; Khalid Aboubakr Hasan Mousay; Mohd Nizam Mohd Talib; Mohd Abdul Talib Mat Yusoh; Mohd Norazysyam Azman (International Journal of Integrated Engineering, 2026)
Oil palm biomass presents considerable potential as a renewable energy source for sustainable agricultural applications. This study develops and evaluates an oil palm biomass-based renewable energy system integrated with an automated irrigation mechanism. Biomass pellets were combusted to generate steam that drives a turbine-dynamo system for electricity production. Experimental results show that the series configuration of two dynamo motors produced the highest output voltage of 5.72 V at 380.36 RPM under no-load conditions and 5.22 V under load, demonstrating superior energy conversion performance compared to single and parallel configurations. The automated irrigation system successfully activated the water pump when soil moisture dropped below 30 percent, ensuring efficient water management and reduced wastage. The system operated stably using a lithium-ion battery for energy storage and supply. Overall, the findings confirm that oil palm biomass pellets are a viable small-scale renewable energy source capable of supporting precision agriculture applications, with strong potential for scalability in sustainable agricultural development.